PENGARUH PERTUMBUHAN PERUSAHAAN TERHADAP KE-BIJAKAN DIVIDEN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2016-2020 - Wulandari, Meliza Novi; Subaida, Ida; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Every company in carrying out its business activities certainly has certain goals and one of them is to make a profit. The purpose of this study was to analyze and test the effect of company growth on dividend policy through profitability. This research is causality research. The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that company growth has a significant positive effect on profitability, company growth has a positive but not significant effect on dividend policy, profitability has a significant positive effect on dividend policy. The results of the indirect effect hypothesis test show that the variable Company Growth on Dividend Policy through Profitability has a negative but not significant effect.